Bull Threshers and Bindlestiffs Harvesting and Threshing on the North American Plains - Isern, Thomas D. (University Press of Kansas, 1990)
Bull Threshers and Bindlestiffs is a panorama on a continental canvas: the Great Plains of North America, stretching from Texas to Alberta. Onto this surface the author lays the large features of regional practice in the harvesting and threshing of wheat during the days before the combined harvester-harvesting with binder and header, threshing with bull thresher and steam engine. Into the picture he places the key figures who accomplished the task of gathering the grain-the farm men and women, the custom threshermen, and the bindlestiffs, or itinerant laborers. Affectionately he sketches the small details of folklife that comprised the everyday work and culture of the wheat belt-building shocks, loading racks, constructing stacks, pitching bundles into the separator, hauling water to the engine, drinking deep from the crockery water jug.Bull Threshers and Bindlestiffs is a profusely illustrated study of a complex, vigorous regional culture concerned with the production of wheat-a culture that centered around the annual harvest and declined with the advent of the combine. This is an examination of the interaction of culture, environment, and technology with import for the fields of agricultural history and regional history. More than that, with its grassroots research, its descriptions of tools and customs, and its lavish illustrations, it is a recreation of a proud phase of regional life previously captured only in yellowed albumen photographs.